2018
DOI: 10.1016/j.ijheatmasstransfer.2017.10.015
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical manifold microchannel heat sink array for high-heat-flux two-phase cooling of electronics

Abstract: High-heat-flux removal is necessary for next-generation microelectronic systems to operate more reliably and efficiently. Extremely high heat removal rates are achieved in this work using a hierarchical manifold microchannel heat sink array. The microchannels are imbedded directly into the heated substrate to reduce the parasitic thermal resistances due to contact and conduction resistances. Discretizing the chip footprint area into multiple smaller heat sink elements with high-aspect-ratio microchannels ensur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(53 citation statements)
references
References 45 publications
1
52
0
Order By: Relevance
“…The coating technique that cover on top of VACNT before complete the TIMs assembly has gained attention from other researchers when dealing with VACNT and found that the coating will help on reducing thermal contact resistance, increasing surface contact between VACNT and heat sink, and maintaining the optimum thermal conductivity . In addition, the reliability of the thermal performance of TIMs is an important factor to be considered.…”
Section: Carbon Allotrope Materials In Tims Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The coating technique that cover on top of VACNT before complete the TIMs assembly has gained attention from other researchers when dealing with VACNT and found that the coating will help on reducing thermal contact resistance, increasing surface contact between VACNT and heat sink, and maintaining the optimum thermal conductivity . In addition, the reliability of the thermal performance of TIMs is an important factor to be considered.…”
Section: Carbon Allotrope Materials In Tims Applicationmentioning
confidence: 99%
“…81 The coating technique that cover on top of VACNT before complete the TIMs assembly has gained attention from other researchers when dealing with VACNT and found that the coating will help on reducing thermal contact resistance, increasing surface contact between VACNT and heat sink, and maintaining the optimum thermal conductivity. 80,[88][89][90] In addition, the reliability of the thermal performance of TIMs is an F I G U R E 6 SEM image of VACNT using PE-CVD 4,83 SEM, scanning electron microscopy; PE-CVD, plasmaenhanced chemical vapor deposition; VACNT, vertically aligned carbon nanotube important factor to be considered. Nylander et al 89 observed the thermal resistance within 100 cycles, where thermal performance was degraded.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…Indeed, high computational power and fast responsiveness generate heat that needs to be dissipated. Heat sinks with brush architecture are one common strategy but require expensive and time‐consuming fabrication . Exploring composite structures using highly thermally conductive particles or ballistic modes for heat dissipation would also push forward the application scope of electronic devices …”
Section: Discussionmentioning
confidence: 99%
“…A peak heat flux of 326 W/cm 2 was obtained using R134a at 16% thermodynamic outlet vapor quality. Drummond et al [11,12] tested a manifoldmicrochannel array of 15 lm wide by 300 lm deep microchannels. Mass fluxes ranging between 1300 and 2070 kg/m 2 s and thermodynamic outlet vapor qualities between À7% and 30% were tested.…”
Section: Literature Surveymentioning
confidence: 99%